Preparação de argilas organofílicas para o desenvolvimento de nanocompósitos a partir de compostos de PVC plastificado - Souza, Michelle Andrade (2009)
Nanocomposites of Plasticized PVC with organoclays have a large potential to improve the thermal resistance of PVC as well as its flame retardancy. However, a great problem in the production of PVC nanocomposites is the decomposition of conventional organic ammonium salts incorporated on the clay which can catalyze PVC degradation and lead to deterioration of thermal, mechanical and optics properties. The aim of this work was preparing organophilic clays with others organic modifiers more thermally stable and comparing with commercial clays, hoping it could improve plastificized PVC thermal properties and to evaluate the structural characterization and thermal, mechanics properties. It were three organic modifiers: two phosphonium salts and a silane agent coupling. The nanocomposites of plastificated PVC with the organoclays were obtained via melt intercalation method using a single screw extruder and a rheometer. The samples were molded by compression into specimens to obtain tensile properties and flammability properties. The thermal stability of nanocomposites was analyzed from Metrastatsystem, TGA and the retardancy flame was analyzed from Cone Calorimeter and oxygen indice. Thermo-gravimetric analysis showed that the thermal decomposition temperatures of these organoclays is superior to that of the ammonium counterpart. In spite of the high thermal resistance of the phosphonium organoclays, the nanocomposites prepared with these oganoclays presented an intense dark appearance and began to degradate in small times, suggesting a strong degradation of PVC. On the other hand, nanocomposites prepared with organoclays modified with silane agent coupling showed an improved thermal resistance, however it hasn´t showed exfoliated structures. The Plasticized PVC Nanocomposite / Cloisite 30B and Plasticized PVC Nanocomposite Nanocor Phosphonium 1 were the systems that shown best moduls compared to pure compound. The decomposition of phosphonium salts don´t promoved injuries on the mechanical properties of these materials. The chemistry structure of organic modifier of Cloisite 30B, containing a functional group OH, improved the exfoliation of this organoclay in the polymeric matrix.